Peran Resiliensi Sebagai Moderator Pada Pengaruh Covid Anxiety Terhadap Motivasi Akademik Dalam Pembelajaran Daring - Kusmawaty Matara; Eka Apristian Pantu (Journal of Social, Culture, and Language, 2024)
The pandemic that occurred had an impact on students' academic motivation in online learning. Covid-19 anxiety is the independent variable and resilience is the moderator variable. This study aims to examine the role of resilience as a moderator in the effect of Covid-19 anxiety on academic motivation. Data collection uses the modified academic motivation scale, fear of coronavirus-19 scale, and the brief resilience scale. The results of the study show that there is a positive effect of Covid-19 anxiety on academic motivation. This study also found that resilience is a moderator variable in the effect of Covid-19 anxiety on academic motivation. Keywords: covid-19 anxiety, resilience, academic motivation